Ostrowski-type inequalities for fuzzy-valued functions and its applications in quadrature theory - Costa, T. M. [UNESP]; Flores-Franulič, A.; Chalco-Cano, Y.; Aguirre-Cipe, I. (Elsevier, 2020)
This study provides a new characterization of the switching points for generalized Hukuhara differentiable fuzzy-valued functions. New results on generalized Hukuhara differential and integral calculus for fuzzy-valued functions are developed.Also some Ostrowski-type inequalities for fuzzy-valued functions are obtained, with which is formulated a new quadrature rules to deal with integral of fuzzy-valued functions and show that our results are better than previous ones. Moreover, numerical examples are provided in order to illustrate the applicability of the mathematical tools developed herein.
Keywords: Fuzzy numerical integration; Fuzzy Ostrowski-type inequalities; Fuzzy-valued functions; Switching points